2023
DOI: 10.1029/2022jd037414
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Model of Soil Aerosol Generation and Vertical Transport During Rainfall

Abstract: Related to human health, a myriad of viruses and microorganisms are adhered on the surfaces of the aerosols and may cause disease to spread widely through the respiratory tract (Chen et al., 2015;Huffman et al., 2013;Joung et al., 2017). It is also one of the main routes of transmission for COVID-19, which has taken a huge toll on the global human existence and economy in recent years (Bale et al., 2022;Firle et al., 2022;Le et al., 2021). An in-depth understanding of the mechanisms of aerosols generation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
(134 reference statements)
0
1
0
Order By: Relevance
“…Aerosols not only damage ecosystems, affect climate change, and cause environmental pollution, but also enter the human body and threaten our health. Much research has been done in this field in order to avoid harm from aerosols to human beings and the environment. At a certain temperature, the vapor is in a state of supersaturation when the pressure of the vapor exceeds its saturation vapor pressure at that temperature; Khakharia et al predicted aerosol emissions after a chemical absorption system using the Aspen Plus model and found that supersaturation was an important factor for predicting aerosol emissions .…”
Section: Introductionmentioning
confidence: 99%
“…Aerosols not only damage ecosystems, affect climate change, and cause environmental pollution, but also enter the human body and threaten our health. Much research has been done in this field in order to avoid harm from aerosols to human beings and the environment. At a certain temperature, the vapor is in a state of supersaturation when the pressure of the vapor exceeds its saturation vapor pressure at that temperature; Khakharia et al predicted aerosol emissions after a chemical absorption system using the Aspen Plus model and found that supersaturation was an important factor for predicting aerosol emissions .…”
Section: Introductionmentioning
confidence: 99%